2000
DOI: 10.1096/fj.14.10.1362
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the epidermal growth factor receptor in epithelial repair in asthma

Abstract: Epithelial damage and airway remodeling are consistent features of bronchial asthma and are correlated with disease chronicity, severity, and bronchial hyperreactivity. To examine the mechanisms that control bronchial epithelial repair, we investigated expression of the epidermal growth factor receptor (c-erbB1, EGFR) in asthmatic bronchial mucosa and studied repair responses in vitro. In biopsies from asthmatic subjects, areas of epithelial damage were frequently observed and exhibited strong EGFR immunostain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
337
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(370 citation statements)
references
References 54 publications
28
337
1
4
Order By: Relevance
“…For example, EGFR plays an essential role in airway inflammation, reflecting epithelial damage and activation, and its expression increases in proportion to the severity of the asthma (Amishima et al, 1998;Puddicombe et al, 2000;Burgel and Nadel, 2004;Wong, 2005). EGFR is a 170-kDa membrane glycoprotein which is activated by multiple ligands including EGF, TGF-, heparin binding (HB)-EGF, amphiregulin, -cellulin, and epiregulin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, EGFR plays an essential role in airway inflammation, reflecting epithelial damage and activation, and its expression increases in proportion to the severity of the asthma (Amishima et al, 1998;Puddicombe et al, 2000;Burgel and Nadel, 2004;Wong, 2005). EGFR is a 170-kDa membrane glycoprotein which is activated by multiple ligands including EGF, TGF-, heparin binding (HB)-EGF, amphiregulin, -cellulin, and epiregulin.…”
Section: Discussionmentioning
confidence: 99%
“…On ligand binding, EGFR homodimerise or heterodimerise, thereby inducing intrinsic kinase activities that initiate intracellular signal transduction cascades including the Ras/Raf/MAPK pathway, the phosphatidylinositol 3-kinase (PI3K)/Akt pathway, and the STAT pathway (Bogdan and Klambt, 2001). The degree of EGFR expression reflects the epithelial damage and activation, and increases in proportion to asthma severity (Amishima et al, 1998;Puddicombe et al, 2000;Burgel and Nadel, 2004;Wong, 2005). Activated EGFR also has an essential role in mucin production in airway epithelium (Takeyama et al, , 2001Nadel, 2001;Nadel and Burgel, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…One well-recognized feature of epithelial alterations in the asthmatic airway is the increased expression of the EGFR and several of its ligands, leading to increased and corticosteroid-insensitive EGFR activation (6)(7)(8)(9)(10). Epithelial EGFR activation contributes to several important features of asthma, including the activation of a chronic wound response within the airways characterized by airway remodeling, mucous metaplasia, and neutrophilic inflammation (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…However, the EGFR signaling pathway is implicated in airway biology and EGFR is expressed by many cell types in the lung, including smooth muscle cells, endothelium, fibroblasts and epithelium [3,4]. Human asthmatic airways show increased EGFR immunoreactivity in airway epithelium, glands, and smooth muscle [5] and EGFR activation has been reported to promote epithelial repair and to induce mucin production and remodeling of airway tissues [6,7]. We previously reported that multiple OVA challenges increased protein expression of the EGFR ligand, heparin-binding EGF-like growth factor (HB-EGF) in airway epithelium in Brown Norway (BN) rats [4].…”
Section: Introductionmentioning
confidence: 99%